Therapeutic Effects of a New “Indigenous Vaccine” Developed Using Novel Native “Indian Bison Type” Genotype of Mycobacterium avium Subspecies paratuberculosis for the Control of Clinical Johne's Disease in Naturally Infected Goatherds in India - S. V. Singh; P. K. Singh; A. V. Singh; J. S. Sohal; M. C. Sharma (Veterinary Medicine International)
Therapeutic efficacy of an “Indigenous vaccine” has been evaluated with respect to a commercial vaccine (Gudair, Spain), for the control of clinical Johne's disease (JD) in naturally infected goatherds. Seventy-one goats (JD positive) were randomly divided into 3 groups (“Bison”, “Gudair” and “Sham-immunized”). After vaccination, goats were monitored for physical condition, morbidity, mortality, body weights, shedding of M. paratuberculosis (MAP) in feces, internal condition and lesions, as well as humoral and cell-mediated immune responses for 210 days. Study showed marked overall improvement in physical condition of vaccinated goats and average body weight gain was significantly higher (P<.05) in “Bison” group as compared to “Sham-immunized” goats. Mortality due to JD was significantly (P<.05) lower in vaccinated groups than in “sham-immunized”. Morbidity rates (due to diarrhea and weakness) were lower in “Bison” group as compared to other groups. Died goats from vaccinated groups showed regression of gross JD lesions and regeneration of fat layer around visceral organs while “Sham-immunized” goats exhibited frank lesions. Vaccinated goats had higher protective CMI response and also higher antibody titer for the trial period as compared to “Sham immunized”. Both vaccines also reduced shedding of MAP in feces significantly (P<.05). Though the two vaccines effectively restricted the severity of clinical symptoms of JD, however “Indigenous vaccine” was superior in many respects.